Exploration of Cultural Values in the Blarak-Blarak Sempal Game: Semiotics of Riffaterre - Fitrianingsih, Anisa Desi; Wulandari, Yosi (Universitas PGRI Semarang, 2025)
This research is motivated by the existence of traditional games, namely the blarak-blarak sempal game. The purpose of this study is to describe the symbols and singing verses in the blarak-blarak sempal game. This study uses qualitative research with a descriptive method. The data taken is in the form of words, phrases, clauses, or sentences from symbols and verses sung by the blarak-blarak sempal game. The results of this study are in the form of signification in symbols and singing verses in blarak-blarak sempal using Riffaterre's semiotic theory, namely matrices, models, variants, hypograms, and heuristic and hermeneutic readings. Based on the semiotic readings of Riffaterre, several symbols such as coconut coir, rotate, hold, leg, and balance were found. In the poems, data such as blarak, inciki, mendal, keplere, sandhung, jekluk, and jenang are found. The symbols and verses of the songs found have significant cultural values such as the value of pleasure or joy, the value of cohesiveness, the value of patience, the value of friendship, the value of leadership, the value of cooperation, the value of togetherness, the value of courage, the value of appreciation, and the value of responsibility. The results of this study reveal various components of cultural values in the blarak-blarak sempal game that show the meaning of interpretation in the symbols and songs sung in the game, especially in the context of Javanese culture.